A STUDY ON TEACHERS’ FEEDBACK TOWARDS THE STUDENTS’ PRONUNCIATION AT SDN 3 PABELAN KARTASURA 2008/ 2009 - Abdillah, Yusuf Fitra (2010)

(untitled)
The research aims at describing the teacher’s feedback in teaching pronunciation and to know the students responses. The result of this study hopefully gives contribution to teaching- learning English especially in teaching pronunciation. This research was carried out at SD N Pabelan 03, Kartasura, especially at the fifth year. To collect the required data, the researcher took all elements of teaching- learning process committed by the teacher, the students and the other sources such as book, syllabus, etc. The methods of collecting data are interview, observation, and documentation. The result of research is that the teacher’s feedback has motivated the students to correct their pronunciation. The teacher gives the students the correct pronunciation so that the students can repeat it correctly. In SD N Pabelan 3 Kartasura the teacher emphasizes the instruction using imperative and practical way. Thus the student’s response enthusiastically to follow the lesson. In addition the teacher gave much attention to students who fell unmotivated.